Stray Load Loss Valuation in Electrical Transformers: A Review - Bonginkosi A. Thango; Pitshou N. Bokoro (Energies, 2022)
The electricity production opus in South Africa has transformed over the last few years from predominantly coal power generation to a blend of renewable energy generation. The necessity emerges to ascertain whether electrical transformer design philosophies in local manufacturers are contemporary in reference to customer specifications, under increasing penetration of harmonics and distortion as a result of increasing deployment of decentralized power systems. Accurate computation of transformer stray load loss is imperative in localizing the hotspot regions and design of adequate insulation system and consequently cooling system. This loss must also be met by manufacturers based on the customer specifications to avoid penalties. The review of current scientific works affirms the ongoing interest in utilizing the advancement of computational power for painstaking evaluation and management of stray load loss in electric transformers. This article confers overview research, evolution and application of diverse computer-based tools for analyzing the stray load loss based on over 60 published scientific works. Mathematical formulations that can be practically employed by transformer designers during the design phase under normal and harmonic load current conditions are discussed.